Multiplex networks in resilience modeling of critical infrastructure systems: A systematic review - Wang, Ying; Zhao, Ou; Zhang, Limao (Reliability engineering & system safety, 2024)
•A systematic review of multiplex network in resilience of interdependent infrastructures.•Three types of interdependencies including proximity, function, and logic.•Research gaps in multi-hazard attacks, high-resolution performance indicators, percolation mechanisms.•Lack systematic evaluation of nature-based and engineering solutions towards infrastructure resilience.•Call for high-quality observation data and informed multi-faced uncertainties. Modeling the effect of extreme events on multiple interdependent critical infrastructure systems (CIS) simultaneously is essential for improving their resilience. To uncover CIS resilience, an increasing number of studies are attempting to incorporate the interdependency in CIS resilience modeling under disaster events, where multiplex network is a powerful and promising representative. This paper presents a systematic review of multiplex networks in CIS resilience modeling and discusses the state of the art on the topic. This review helps to guide the construction of multiplex networks in CIS with different types of interdependencies and highlights the key aspects of CIS resilience modeling including attacks, evaluation, evolution, and control. Moreover, several challenges are identified while providing possible future research directions. The findings and discussions of this study could be helpful to researchers and professionals in the field of CIS resilience modeling especially when leveraging multiplex networks.